Why does the Caribbean Periwinkle Escape Rock Surrounded by Seawater? - Hoogerdyk, Ariana (SciWise, 2025)
The beaded periwinkle (Cenchritis muricatus), a semi-terrestrial Caribbean snail, is on coastal supratidal rocks exposed to seawater, rainwater, and hot, dry conditions. Earlier experiments indicated that periwinkles alter their activity in response to seawater. However, those experiments were inconclusive regarding why periwinkles often escaped overnight from rocks surrounded by seawater but not freshwater. We aimed to identify the potential drivers of this behaviour and examine the influence of other factors, such as rock height, terrain type, water depth, rock surface area, and salinity level. Consistent with past findings, periwinkles migrated away from rocks surrounded by seawater more frequently than freshwater, regardless of the other factors tested. Although some factors may have ecologically meaningful modulating effects, the high variance and low treatment replication in this study prevented drawing definitive conclusions about their roles. Despite these limitations, the findings provide insight into the resilience of periwinkles and their behavioural responses. Furthermore, because we found no apparent benefits from the behaviour of escaping the home rock when surrounded by seawater, we propose that the interpretation requires considering a long temporal scale at which storm exposure may be a strong selection factor, eliciting behaviours less likely to produce benefits under standard conditions. Illustrator: Erin Zhang